2021
DOI: 10.24875/ciru.20000916
|View full text |Cite
|
Sign up to set email alerts
|

Parálisis facial, causas y tratamiento quirúrgico en un centro de referencia en cirugía plástica y reconstructiva en México

Abstract: Antecedentes: La parálisis facial es una afección incapacitante que con frecuencia causa un impacto negativo en los aspectos cosméticos, funcionales, sociales, psicológicos y económicos. El tratamiento quirúrgico tiene como objetivo mejorar la calidad de vida dejando la menor cantidad posible de secuelas. Objetivo: Describir la experiencia del manejo quirúrgico y proponer un algoritmo de tratamiento. Método: Se realizó un estudio retrospectivo, de 2017 a 2019, de los expedientes de pacientes con afección del n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Individuals who suffer from FP might have difficulty to make coordinated expressions, eating disorder and increasing risk of ocular inflammation [5]. Moreover, those people with severe FP or in acute phase present facial asymmetry, which might hinder their abilities of communication and social cognition, even lead to psychosomatic problems [6]. It is reported that patients with FP often experienced negative emotions such as anxiety, depression and low self-esteem and their quality of life would also be greatly affected [7].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who suffer from FP might have difficulty to make coordinated expressions, eating disorder and increasing risk of ocular inflammation [5]. Moreover, those people with severe FP or in acute phase present facial asymmetry, which might hinder their abilities of communication and social cognition, even lead to psychosomatic problems [6]. It is reported that patients with FP often experienced negative emotions such as anxiety, depression and low self-esteem and their quality of life would also be greatly affected [7].…”
Section: Introductionmentioning
confidence: 99%